Temporal Expression Analysis of the Borrelia burgdorferi Paralogous Gene Family 54 Genes BBA64, BBA65, and BBA66 during Persistent Infection in Mice - Gilmore, Robert D. (American Society for Microbiology, 2007)
Members of the Borrelia burgdorferi paralogous gene family 54 (pgf 54) are regulated by conditions simulating mammalian infection and are thought to be instrumental in borrelial host survival and pathogenesis. To explore the activities of these genes in vivo, a comprehensive analysis of pgf 54 genes BBA64, BBA65, and BBA66 was performed to assess the genetic stability, host antibody responses, and kinetics of gene expression in the murine model of persistent infection. DNA sequencing of pgf 54 genes obtained from reisolates at 1 year postinfection demonstrated that all genes of this family are stable and do not undergo recombination to generate variant antigens during persistent infection. Antibodies against BBA64 and BBA66 appeared soon after infection and were detectable throughout the infection, suggesting that there was gene expression during infection. However, quantitative reverse transcription-PCR revealed that BBA64 gene expression was considerably decreased in Borrelia residing in the mouse ear tissue compared to the expression in cultured spirochetes by 20 days postinfection and that the levels of expression remained low throughout the infection. Conversely, transcription of the BBA65 and BBA66 genes was increased, and both of these genes were continuously expressed until 100 days postinfection; this was followed by periods of differential expression late in infection. The expression profile of the BBA64 gene suggests that this gene has an important role during tick-to-host transmission and early infection, whereas the expression profile of the BBA65 and BBA66 genes suggests that these genes have a role in persistent infection. The differential regulation of pgf 54 genes observed during infection may help confer a survival advantage during persistent infection, influencing mechanisms for B. burgdorferi dissemination, tissue tropism, or evasion of the adaptive immune response.